2012
DOI: 10.1007/s00120-012-2837-2
|View full text |Cite
|
Sign up to set email alerts
|

Das urologische Dyna-CT

Abstract: Apart from standard urological imaging such as fluoroscopy, intravenous pyelography or plain abdominal X-ray the urological Dyna-CT enables further imaging of the urinary tract. Fluoroscopy sequences can be stored as videos, and 3-D reconstructions of the urinary tract are possible with permanent patient access for any intervention. Extensive tests led to the technical approval of the system in urology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…CBCT has recently been adopted in urology. It has been used for the intraoperative assessment of the stone-free status [10,11,12] or for guiding percutaneous access to the kidney [13]. A recent article from our center described the outcome of our rst 102 cases in which CBCT was used for detecting residual fragments intraoperatively during PCNL [14].…”
Section: Introductionmentioning
confidence: 99%
“…CBCT has recently been adopted in urology. It has been used for the intraoperative assessment of the stone-free status [10,11,12] or for guiding percutaneous access to the kidney [13]. A recent article from our center described the outcome of our rst 102 cases in which CBCT was used for detecting residual fragments intraoperatively during PCNL [14].…”
Section: Introductionmentioning
confidence: 99%
“…Several publications have already stated the possible benefits of CBCT for detecting residual stones in PCNL [ 14 , 15 ], or have already reported on cases in which CBCT was used for this purpose [ 16 ]. However, there are not much data available about the added value of the CBCT-scanner for detecting and extracting residual fragments.…”
Section: Introductionmentioning
confidence: 99%
“…CBCT has recently been introduced in urology. It has been described in PCNL for the use of needle guidance for gaining percutaneous acces s[ 12 , 13 ] or for the detection of residual stones [ 14 ]. A recently published paper describing a study conducted in our center demonstrated the feasibility of CBCT for the detection of residual stones in PCN L[ 15 ].…”
Section: Introductionmentioning
confidence: 99%